Highlights in cellular and molecular mechanisms of allergic diseases - XXVth Congress of the European Academy of Allergology and Clinical Immunology in Vienna - (:unkn) unknown (KARGER, 2007)
This year, the annual congress of the European Academy of Allergology and Clinical Immunology was held on 10-14 June in Vienna. More than 6,000 delegates, practicing bench or bedside work or both, gathered from over 50 countries throughout the world. Health professionals, basic scientists and fellows in training could choose between a variety of activities in plenary, main, educational and workshop sessions, highlights of the past year, pros and cons, and oral abstract and poster sessions, and met with experts. A total of 1,713 abstracts, 31 symposia, and 54 workshops were presented, ranging from basic science to clinical trials and modern treatment of allergic diseases. Here, we summarize the highlights of cellular and molecular mechanisms of allergic disease. Copyright (c) 2007 S. Karger AG, Basel
Keywords: immune regulation; inflammation; T cells; B cells; dendritic cells; T regulatory; IgE; transcription factors; REGULATORY T-CELLS; GROWTH-FACTOR; INFLAMMATION; ACTIVATION; EXPRESSION; RECEPTORS; RAPAMYCIN; IMMUNITY; LINEAGE; BETA